Hypermarkets in Malaysia: Issues of Expansion, Distribution and Corporate Social Responsibility - Ghaffarkadhim, Kadhim; Harun, Amran; Abdulmaged Othman, Bestoon (International Journal of Psychosocial Rehabilitation, 2019)
With the higher consideration of Corporate Social Responsibility among researchers globally, its empirical support in Malaysia is relatively limited. In fact, various factors have proven to impact CSR application that eventually leads to increase customer base and win their satisfaction and loyalty. Moreover, CSR practices are key concern area for hypermarkets to ensure their business sustainability in a changing and uncertain corporate environment. Business corporations are currently seeking higher social responsibility that contributes to the environment and society. Additionally, Hypermarkets consider higher degree of CSR practices to impact the behavior of their consumers. Consequently, the aim of this paper is to discuss in details issues regarding expansion, distribution, and challenges met by Malaysian hypermarkets CSR practices.